Regulation of Hippo-YAP1/TAZ pathway in metabolic dysfunction-associated steatotic liver disease - Xuan, Wei; Song, Dandan; Hou, Jianghua; Meng, Xiuping (Frontiers in Pharmacology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) has become the most prevalent chronic liver disease worldwide, but effective treatments are still lacking. Metabolic disorders such as iron overload, glycolysis, insulin resistance, lipid dysregulation, and glutaminolysis are found to induce liver senescence and ferroptosis, which are hot topics in the research of MASLD. Recent studies have shown that Hippo–YAP1/TAZ pathway is involved in the regulations of metabolism disorders, senescence, ferroptosis, inflammation, and fibrosis in MASLD, but their complex connections and contrast roles are also reported. In addition, therapeutics based on the Hippo–YAP1/TAZ pathway hold promising for MASLD treatment. In this review, we highlight the regulation and molecular mechanism of the Hippo–YAP1/TAZ pathway in MASLD and summarize potential therapeutic strategies for MASLD by regulating Hippo–YAP1/TAZ pathway.